Strategic Management Process of Islamic Character Development of Early Children in Islamic Kindergarten - M Najib; Novan Ardy Wiyani (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2016)
This research is a field research by using a qualitative research approach. The purpose in this research is to find steps in strategic management process for development character of early children in Islamic kindergarten of al-Irsyad Purwokerto, Central java, Indonesia. The results showed that the process of strategic management to develop Islamic character of early children is done through four processes. First, processing of observation environmental to develop Islamic character in Islamic kindergarten. Second, strategic formulation process for development an Islamic character of early children in Islamic kindergarten. Third, implementating strategic process for develop an Islamic character of early children in Islamic kindergarten. Fourth, strategic assesment process for develop an Islamic character of early children in Islamic kindergarten.Penelitian ini adalah penelitian lapangan menggunakan pendekatan penelitian kualitatif. Tujuan dari penelitian ini adalah untuk menemukan langkah-langkah dalam proses manajemen strategik untuk membentuk karakter anak usia dini di Taman Kanak-kanak (TK) Islam al-Irsyad Purwokerto, Jawa Tengah, Indonesia. Hasil penelitian mengungkapkan bahwa proses manajemen strategik untuk membentuk karakter anak usia dini di TK Islam dilakukan melalui empat langkah. Pertama, proses pengamatan lingkungan untuk membentuk karakter Islami anak usia dini di TK Islam. Kedua, proses formulasi strategi untuk membentuk karakter anak usia dini di TK Islam. Ketiga, proses penerapan strategi untuk membentuk karakter anak usia dini di TK Islam. Keempat, proses penilaian strategik untuk membentuk karakter anak usia dini di TK Islam.